The role of cold work and applied stress on surface oxidation of 304 stainless steel - Lozano-Perez, S; Kruska, K; Iyengar, I; Terachi, T; Yamada, T (2012)
FIB 3-dimensional (3D) sequential sectioning has been used to characterize environmental degradation of 304 stainless steels in pressurized water reactor (PWR) simulated primary water. In particular, the effects of cold work and applied stress on oxidation have been studied in detail. It was found that a description of the oxidation behaviour of this alloy is only complete if it is treated statistically, since it can suffer from high variability depending on the feature described. © 2011 Elsevier Ltd.